Fibularis tertius muscle among first and second year medical and dental students of a medical college: a descriptive cross-sectional study - Pandit, Ruku; Upadhyay, Hari Prasad; Sharma, Nitasha (Journal of Chitwan Medical College, 2021)
Background: The fibularis tertius muscle (FTM) is a variant muscle of the crural compartment of the leg that is thought to have evolved in human as a result of the development of the bipedal gait. The Fibularis tertius muscle, as an ankle dorsiflexor and foot evertor, plays an important physiological role in effective terrestrial locomotion related to midfoot biomechanical stabilization. The objective of this study is to determine the occurrence of the fibularis tertius muscle using a surface anatomical examination of the foot in medical and dental students of a medical college. Methods: This was a descriptive cross-sectional study comprising 294 pre-clinical medical and dental students of College of Medical Sciences, Chitwan, Nepal. In each student, the fibularis tertius muscle was palpated on both lower limbs for their presence or absence. The data was collected in terms of age and gender and was analyzed using the Statistical Package for Social Science version 20. Results: The prevalence of fibularis tertius muscle was 50.68%, with females accounting for 23.13% and males accounting for 27.55%. Fibularis tertius muscle was more common bilaterally (37.07%) than unilaterally (13.61%). Among unilateral fibularis tertius muscle, 24 (8.16%) were found only on the right foot and 16 (5.44%) on the left foot only. The bilateral prevalence of the fibularis tertius muscle was 17.01 % in females and 20.07 % in males, while its unilateral prevalence in females and males was 6.12 % and 7.48 %, respectively. Conclusions: The involvement of the fibularis tertius muscle in affecting midfoot stabilization and its potential role in delaying the healing process of John’s fracture cannot be ignored. Hence, understanding the theory behind foot biomechanics requires awareness of the existence of the fibularis tertius muscle.